IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) PADA SEKOLAH NU DAN MUHAMMADIYAH - Munjahid (AN NUR: Jurnal Studi Islam, 2013)
Masyithah’s kindergarten Bandung Sewon Bantul (TK NU) and ABA’s kindergarten Nitikan Yogyakarta (TK Muhammadiyah) are two kindergartens implement total quality management. Both of the kindergartens, which equally Islam has been accredited with a rating of A. However, both Kindergartens were organized by two Islamic organizations, namely NU and Muhammadiyah. Both kindergarten above both use total quality management but with drip at a series of implementation on a different domain. The impact of the implementation of total quality management in both the kindergartens are the achievement of the vision, mission and goal. Difference in both of kindergartens is that the progress made by Masyithah’s kindergarten are slowly but surely (evolution), while progress has been made in Nitikan ABA’s Kindergarten is dynamic.